Problematika Kebijakan Penindakan Pelanggaran Lalu Lintas pada Anak di Masa Pandemi Covid-19 - Muhammad, Hasanuddin; Putri, Rika Rahmanisa; Zuhraini, Zuhraini; Alimuddin, Agus (Universitas Islam Negeri Raden Intan Lampung, 2022)
The policy problem of enforcing traffic violations by children during the Covid-19 pandemic is important to discuss based on the impact on the safety of children and the safety of others. The safety impacts are both caused by the threat of accidents and the threat to safety due to the spread of Covid-19. Specifically, this study will address the policy problems of enforcing traffic violations against children during the Covid-19 pandemic in three aspects, namely positive legal aspects, Islamic law and legal culture. This research was conducted at the Tulang Bawang Police Resort by interviewing the traffic department and studying traffic violation documents. Data analysis uses an analytical normative approach based on positive legal theory, Islamic law and legal culture. Legally, the enforcement of traffic violations by children during the Covid-19 pandemic is based on policy regulations. Legally, the policy is positive in accordance with the provisions of the Government Administration Act. According to Islamic law, the policy contains dharuriyat matters and culturally the law of children and their parents as well as law enforcement officers to put forward a culture of obeying the law.